Translating Magic and Preserving Meaning in the Cross-Linguistic Translation of Speaking Names in Harry Potter and the Philosopher’s Stone: - Nemickienė, Živilė (Technium Education and Humanities, 2025)
This study examines how “speaking names” in Harry Potter and the Philosopher’s Stone are translated across eleven languages, with a focus on Lithuanian, Russian, Italian, and Chinese. Drawing on Vlakhov and Florin’s taxonomy of realia, Venuti’s foreignization/domestication framework, Skopos theory, and literary onomastics, it evaluates the balance between phonetic fidelity and semantic adaptation. The corpus comprises 56 names (43 characters, 4 places, 9 objects/creatures), analysed by narrative role and assessed using a symbolic gain/loss scale from −2 (complete loss) to +2 (strong enrichment). Findings show distinct cultural and institutional translation logics: Lithuanian consistently employs semantic enrichment aligned with pedagogical norms, Russian favours phonetic fidelity to preserve brand identity, Italian uses metaphorical substitution to reinforce character traits, and Chinese blends phonetic and semantic cues to enhance resonance. East Asian translations tend toward symbolic flattening due to script constraints, while Western European languages show greater flexibility in preserving narrative tone and metaphorical nuance. The results highlight the translator’s dual role as linguistic mediator and cultural curator, demonstrating how children’s literature translation is shaped by educational traditions, market demands, and global brand strategies. The proposed symbolic scoring framework offers a replicable tool for assessing the narrative and cultural shifts in literary onomastics.